2015
DOI: 10.1142/s0129065715500148
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Fusion for the Prediction of Self-Initiated Fine Movements from Single-Trial Readiness Potentials

Abstract: Current human-machine interfaces (HMIs) for users with severe disabilities often have difficulty distinguishing between intentional and inadvertent activations. Pre-movement neuro-cortical activity may aid in this elusive discrimination task but has not been exploited in HMIs. This work investigates the utility of the readiness potential (RP), a slow negative cortical potential preceding voluntary movement, for detecting the intention of self-initiated fine movements prior to their motoric realization. We reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Nikjoo et al (2011) suggested a reputation-based classification in which the decision of each classifier was weighed on the basis of its past performance. In this work, we use the reliability weighted average (RWA) technique (Abou Zeid and Chau, 2015). It weights the classification algorithms by their validation accuracies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nikjoo et al (2011) suggested a reputation-based classification in which the decision of each classifier was weighed on the basis of its past performance. In this work, we use the reliability weighted average (RWA) technique (Abou Zeid and Chau, 2015). It weights the classification algorithms by their validation accuracies.…”
Section: Methodsmentioning
confidence: 99%
“…Following the estimation of the class-conditional Gaussian distributions from training data, Bayes' theorem is used to infer the posterior probability of a test case belonging to a certain class. We presented a complete mathematical formulation of LPGM in Abou Zeid and Chau (2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a neuron’s firing rate, or the rate at which action potentials are generated, is known to be information-rich. This firing rate is used to decode or interpret complex behaviors of a subject such as movement (Carmena et al, 2003; Lebedev et al, 2005; Abou Zeid and Chau, 2015; Suberbiola et al, 2015; Villar et al, 2016), slow eye movements (Takemura et al, 2001; Ghahari and Enderle, 2014), attention (Ecker et al, 2016), or memory recall (Janetsian et al, 2015) among others. The relationship between firing rate and behavior can be made directly via correlation (Takemura et al, 2001), or indirectly using triggered averaging schemes to observe the contribution of a neuron to the recruitment of a particular muscle (Davidson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%